Effects of neurofeedback training on frontal midline theta power, shooting performance, and attentional focus with experienced biathletes - Toolis, T.; Cooke, A.; Laaksonen, M. S.; McGawley, K. (Journal of Clinical Sport Psychology, 2024)
Frontal midline theta power (FMT) has been associated with superior rifle shooting performance. Our experiment examined whether electroencephalographic-based training could increase FMT, shooting performance, and attentional focus in highly trained/elite biathletes. Participants (n = 28; age, M = 21.7, SD = 2.3) were assigned to a control group or an intervention group (with 3 hr of neurofeedback training). FMT increased from baseline during the neurofeedback training sessions (p = .05). However, there were no Group × Pre-post training (test) interactions for FMT or shooting performance (p > .05). There was a small Group × Test effect for attentional focus (p = .07, ?2p=.12), indicating a potential benefit of neurofeedback training. Superior shooters were more proficient at increasing FMT during neurofeedback training, but this did not translate to greater improvements in shooting performance. Our findings suggest that the effects of neurofeedback training are transient and do not necessarily benefit performance.